Estudio de prefactibilidad para la instalación de una planta para la elaboración de chicha de jora con maca y chancaca en six-pack de latas de 255 ml (Zea mays y Lepidium meyenii) - Carbonel Dominguez, Miguel Antonio (2023)
We began by raising the problem, proposing objectives, the scope of the investigation, justifications analyzing investigations that are related to the chosen topic to clearly understand the needs of the project and how to proceed in the following chapters. In addition, the most used concepts are mentioned, as well as the engineering tools. In the second chapter, the product is defined at the three required levels, in addition analyzing the Porter forces, the business model is proposed, and the apparent internal demand analyzed, which, with the help of the results of the survey and the expected participation, will determine the demand for the project, obtained this from defining the marketing strategies. In the third chapter, the most important factors for the location of the plant are defined and subsequently the confrontation tables are made that define the importance of each of these, ending in the evaluation of each alternative with the specified scale and weights found above. After this, the size of the plant is selected, taking into consideration the size-market, size-productive resources, size-technology, size-equilibrium point, and based on this, the optimal size with which the production can be met was chosen. commercial demand. In the fifth chapter, the entire study regarding engineering, technical definition, production process, installed capacity, quality assurance, environmental impact study, occupational health and safety, machinery, plant layout, production schedule, among others. For the sixth chapter, the formation of the business organization is defined, defining the requirements of the main positions for the company and finally a complete organization chart is made. Within the seventh chapter, the investments, production costs, operating and financial budgets are detailed to carry out the economic and financial evaluation of these and thus obtain the values VAN, TIR, Cost benefit and recovery period, in addition to evaluating the main financial ratios. Finally, in the eighth chapter, the social evaluation is carried out through indicators of added value, capital density, labour productivity, capital intensity, capital product ratio.